Klotho, an anti-aging gene, acts as a tumor suppressor and inhibitor of IGF-1R signaling in diffuse large B cell lymphoma. Issue 1 (December 2017) - Zhou, Xiangxiang; Fang, Xiaosheng; Jiang, Yujie; Geng, Lingyun; Li, Xinyu; Li, Ying; Lu, Kang; Li, Peipei; Lv, Xiao; Wang, Xin
Abstract Background Klotho, is a transmembrane protein, performs as a circulating hormone and upstream modulator of the insulin-like growth factor-1 receptor (IGF-1R), fibroblast growth factor (FGF), and Wnt signaling pathways. These pathways are involved in the development and progression of B cell lymphoma. We aimed to explore the expression pattern and functional mechanism of Klotho in diffuse large B cell lymphoma (DLBCL). Methods Immunohistochemistry (IHC) and western blotting were performed to detect the expression level of Klotho in DLBCL patients and cell lines. Tumor suppressive effect of Klotho was determined by both in vitro and in vivo studies. Signaling pathway activity was assessed by western blotting. Results Remarkable lower expression levels of Klotho were observed in DLBCL patients and cell lines. Enforced expression of Klotho could significantly induce cell apoptosis and inhibit tumor growth in DLBCL. Upregulation of Klotho resulted in declined activation of IGF-1R signaling, accompanied with decreased phosphorylation of its downstream targets, including AKT and ERK1/2. Moreover, xenograft model treated with either Klotho overexpression vector or recombinant human Klotho administration presented restrained tumor growth and lower Ki67 staining. Conclusions Our findings establish that Klotho performs as a tumor suppressor and modulator of IGF-1R signaling in DLBCL. Targeting Klotho may provide novel strategies for future therapeutic intervention.